Biosynthesis and trafficking of heme o and heme a: new structural insights and their implications for reaction mechanisms and prenylated heme transfer. (2nd November 2021) - Rivett, Elise D.; Heo, Lim; Feig, Michael; Hegg, Eric L.
Abstract: Aerobic respiration is a key energy-producing pathway in many prokaryotes and virtually all eukaryotes. The final step of aerobic respiration is most commonly catalyzed by heme-copper oxidases embedded in the cytoplasmic or mitochondrial membrane. The majority of these terminal oxidases contain a prenylated heme (typically heme a or occasionally heme o ) in the active site. In addition, many heme-copper oxidases, including mitochondrial cytochrome c oxidases, possess a second heme a cofactor. Despite the critical role of heme a in the electron transport chain, the details of the mechanism by which heme b, the prototypical cellular heme, is converted to heme o and then to heme a remain poorly understood. Recent structural investigations, however, have helped clarify some elements of heme a biosynthesis. In this review, we discuss the insight gained from these advances. In particular, we present a new structural model of heme o synthase (HOS) based on distance restraints from inferred coevolutionary relationships and refined by molecular dynamics simulations that are in good agreement with the experimentally determined structures of HOS homologs. We also analyze the two structures of heme a synthase (HAS) that have recently been solved by other groups. For both HOS and HAS, we discuss the proposed catalytic mechanisms and highlight how new insights into the heme-binding site locations shed light on previously obtained biochemical data. Finally, we explore the implications of the new structural data in the broader context of heme trafficking in the heme a biosynthetic pathway and heme-copper oxidase assembly.